Kualitas Kepribadian Pekerja (santri): Etos Kerja dan Disiplin Kerja dan Pengaruhnya terhadap Iltizam Bil Jamaah - Mochamad Noval Nasrudin (FADZAT: Jurnal Ekonomi Syariah, 2021)
The purpose of this study was to examine and analyze the simultaneous, partial and dominant effect of the work ethic and work discipline variables on Iltizam bil Jama'ah. This research is explanatory (explaining) is "to test the hypotheses of a cause-and-effect relationship between the symptoms (variables) being studied. The type of data used is the type of quantitative data which is quantified using a Likert scale. The research population is the population in this study were 59 people. Data analysis used multiple linear regression. The results showed that: 1) Work ethic and work discipline had a simultaneous effect on Iltizam bil Jama'ah. 2) Work ethic has no partial effect on Iltizam bil Jama'ah and work discipline has a partial effect on Iltizam bil Jama'ah 3) Work discipline has a dominant effect on Iltizam bil Jama'ah.